Drug design: 4-thiazolidinones applications. Part 1. Synthetic routes to the drug-like molecules (Journal of Medical Science, 2020)
4-Thiazolidinones, as examples of privileged scaffolds, have been the focus of medicinal chemistry since 60th. Among them, 5-substituted thiazolidinones with a C5 exocyclic bond (5-ene derivatives) are of special interest due to chemical characteristics and pharmacological profiles, possessing anticancer, antimicrobial, and antiviral properties, as well as being high-affinity ligands to a number of biological targets. A new medicinal chemistry trend claims that the aforementioned compounds are frequent hitters or pan assay interference compounds, which are useless because of the possible low selectivity. This is argued by the Michael acceptor property of 5-ene-4-thiazolidinones, which is actively discussed in the literature and requires further investigation. Based on SAR analysis, the main vectors for the design of 5-ene-4-thiazolidinone-based molecules were proposed: complication of C5 fragment; introduction of the substituents in the N3 position; synthesis of isosteric heterocycles; combination with other pharmacologically attractive fragments; annealing of thiazolidinone core; utilisation of 5-ene-thiazolidinones in synthesis of other compounds. The affinity of 5-ene-4-thiazolidinones toward various targets can be regarded as an advantage in polypharmacological approaches. Michael acceptors are considered as the “new old tool” for new drug creation, especially anticancer agents. One of the possible solutions within privileged substructure-based diversity-oriented synthesis is the fixation of 5-ene-4-thiazolidinone fragment in the fused heterocycles, for example, thiopyrano[2,3-d]thiazoles obtained from 5-ene-thiazolidinones.